COMMUNICATION MANAGEMENT OF THE DEAF COMMUNITY IN INDONESIA PPPA DAARUL QUR'AN D.I. YOGYAKARTA: Communication management, Deaf reciting, and PPPA Darul Qur'an. - Diah Fitriatus Sholihah; Sa’diyah El Adawiyah (EKOSSISTEM : Islamic Economics, Banking, Law, System, 2025)
The Islamic religious education for Deaf Muslims in Indonesia faces various complex challenges, resulting in unequal access to education for deaf and illiterate Muslims. The purpose of the research was to analyze communication management in the Deaf Teaching program. There is research on the descriptive qualitative approach used at the research locus at PPPA Daarul Qur'an Yogyakarta, which is the center of Qur'an education for the Deaf community. Primary data sources were obtained through face-to-face interviews and Zoom media. The results show that planned and inclusive communication management has a significant impact on the education of the Deaf community. In addition, the process of systematic planning and adaptive implementation creates a learning environment that supports growth and active participation. Applying research on the use of visual technology and sign language, the program of the deaf community in Yogyakarta not only meets the needs of religious education but also empowers individuals in the deaf community. The output of this study proves that inclusive and adaptive education can change social dynamics and increase access for people with disabilities.